A systematic review of localization, surgical treatment options, and outcome of insulinoma - Mehrabi, Arianeb; Fischer, Lars; Hafezi, Mohammadreza; Grenacher, Lars; Diener, Markus K.; Fonouni, Hamidreza; Golriz, Mohammad; Garoussi, Camelia; Rahbari, Nuh Nabi; Büchler, Markus W. (Pancreas, 2014)
Objective: Insulinoma with an incidence of 0.4% is a rare pancreatic tumor. Preserving surgery is the treatment of choice. Exact localization is necessary to plan the appropriate approach. This article gives an overview on localization and surgical strategies for treatment of insulinoma. Methods: In this systematic review, 114 articles with 6222 cases of insulinoma were reviewed with emphasis on localization techniques and surgical treatment. Results: Insulinoma happens mostly in the fifth decade of life, with a higher incidence in men. They occur mostly sporadic (94%), benign (87%), and single (90%). Insulinomas are mostly smaller than 20 mm (84%). The tumors are distributed almost equally in the pancreas. Conclusions: Computed tomography is routinely used as first choice preoperatively. Intraoperative inspection, palpation, and sonography were applied with high success rate. Intraoperative sonography is considered as the most reliable technique. Enucleation is the most administered type of surgery (56%). Different types of resection include distal pancreatectomy (32%), Whipple procedure (3%), and subtotal pancreatectomy (<3%). Despite the development of laparoscopy, open approach is the favorite method (90%). The most common surgical complication is fistula. The mortality rate of open approach was higher (4vs0%). Despite high cure rate, recurrence of insulinoma occurs in 7% after surgery.